2006
DOI: 10.1021/jf052546g
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cultivation Site on Sesquiterpene Lactone Composition of Forage Chicory (Cichorium intybusL.)

Abstract: The forage potential of chicory (Cichorium intybus L.) has not been realized in southern West Virginia (WV) because ruminants are reluctant to consume the herbage. Chicory contains bitter sesquiterpene lactones that can adversely impact palatability. This study was undertaken to determine whether sesquiterpene lactone concentrations in chicory grown in southern WV differ from those in chicory grown in central Pennsylvania (PA) where chicory is grazed readily. Herbage was collected in 1997 and 1998 from cultiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 33 publications
3
35
1
Order By: Relevance
“…As observed in the present study, the highest total SL concentration was determined in Sugarloaf samples, followed by Radicchio and endive accessions. Higher SL concentrations in comparison to our results were found by Foster et al (2006) in three forage chicory cultivars cultivated in Pennsylvania and West Virginia on two subsequent years.…”
Section: Sesquiterpene Lactones (Sl)contrasting
confidence: 75%
“…As observed in the present study, the highest total SL concentration was determined in Sugarloaf samples, followed by Radicchio and endive accessions. Higher SL concentrations in comparison to our results were found by Foster et al (2006) in three forage chicory cultivars cultivated in Pennsylvania and West Virginia on two subsequent years.…”
Section: Sesquiterpene Lactones (Sl)contrasting
confidence: 75%
“…Nevertheless, they did not report any quantitative data about the distribution of SL in chicory varieties or an evaluation of the effectiveness of the method in recovering SL. In a recent study about the effect of cultivation site on SL composition of forage chicory, Foster et al (2006) employed the same analytical procedure reported by Tamaki et al (1995) but even in this case the levels of saturated SL was not evaluated. In ten forage chicory cultivars, LAT, 8-DELAT, PICR and total SL were at levels of 420-3650, 430-3960, 530-9360, and 1770-15,240 mg/kg of dry matter, respectively.…”
Section: Selection Of the Solvent System Optimising Sl Extractionmentioning
confidence: 99%
“…SL extraction from several Asteraceae species has been carried out by means of different solvents or solvent mixtures such as water (Poli et al, 2002), methanol (Foster et al, 2006;Michalska et al, 2009), ethyl acetate/methanol/chloroform/ethanol (Van Beek et al, 1990), water/methanol (Leven & Willuhn, 1987), ethanol (Kisiel & Michalska, 2008;Ortet, Prado, Mouray, & Thomas, 2008;Schmidt, Ilic, Poulev, & Raskin, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…385 The influence of the cultivation site on the guaianolide composition of Cichorium intybus has been studied. 386 Some of the lactones isolated from Eupatorium capillifolium showed potent inhibitory effects on the growth of HeLa cells, 387 whilst cynaropicrin has been shown to be a potent and irreversible inhibitor of the antibacterial target enzyme MurA. 257 The biotransformation of dehydrocostuslactone by the fungus Mucor polymorphosporus has been investigated.…”
Section: This Journal Is © the Royal Society Of Chemistry 2007mentioning
confidence: 99%